Concurrent influence of top-down and bottom-up inputs on correlated activity of Macaque extrastriate neurons - Merrikhi, Yaser (Nat Commun, 2018)
Correlations between neurons can profoundly impact the information encoding capacity of a neural population. We studied how maintenance of visuospatial information affects correlated activity in visual areas by recording the activity of neurons in visual area MT of rhesus macaques during a spatial working memory task. Correlations between MT neurons depended upon the spatial overlap between neurons’ receptive fields. These correlations were influenced by the content of working memory, but the effect of a top-down memory signal differed in the presence or absence of bottom-up visual input. Neurons representing the same area of space showed increased correlations when remembering a location in their receptive fields in the absence of visual input, but decreased correlations in the presence of a visual stimulus. This set of results reveals the correlating nature of top-down signals influencing visual areas and uncovers how such a correlating signal, in interaction with bottom-up information, could enhance sensory representations.